Frailty in Elderly Patients with Covid-19: A Narrative Review. (17th February 2022) - Salini, Sara; Russo, Andrea; De Matteis, Giuseppe; Piccioni, Andrea; Della Polla, Davide; Carbone, Luigi; Barillaro, Christian; Landi, Francesco; Franceschi, Francesco; Covino, Marcello
Introduction: The SARS CoV-2 pandemic still generates a very high number of affected patients and a significant mortality rate. It is essential to establish objective criteria to stratify COVID-19 death risk. Frailty has been identified as a potential determinant of increased vulnerability in older adults affected by COVID-19, because it may suggest alterations of physical performance and functional autonomy. Methods: We have conducted a narrative review of the literature on the evidences regarding COVID-19 and the frailty condition. Thirteen observational studies were included. Conclusion: Data emerging from the studies indicate that older COVID-19 patients with a frailty condition have an increased risk of mortality compared with non-frail patients, and this association is independent of other clinical and demographic factors. A frailty evaluation is required to help clinicians to better stratify the overall risk of death for older patients with COVID-19.